O Processo de causativização de inergativos e inacusativos no português brasileiro : por uma abordagem nanossintática - Ferreira, Thayse Letícia (2017)
The causative relation has been, for centuries, an interesting source of research in the most di erent areas of knowledge. In this dissertation, we investigated the possibility of certain unergative and unaccusative verbs to express causality, although not being causatives in their base, such as the children sat on the oor Ð→ the mom sat the children on the oor . Our proposal is that the causativization phenomenon is a syntactic mechanism by which the events can receive a (direct) causative interpretation in the situational domain ([ cause P]). The analysis is developed on the basis of Nanosyntax assumptions (Starke, 2009) and demonstrates the role of the terminals of the event domain, the Spell-out rules and the lexical-encyclopedic knowledge in the license of the causativization process in Brazilian Portuguese.